Ethical Hacking Workshop Explore a practical approach to learning and applying ethical hacking techniques for effective cybersecurity - Pillay, Rishalin; Pillay, Rishalin; Abutheraa, Mohammed (Packt Publishing, 2023)
Get a hands-on training and experience in tools, techniques, and best practices for effective ethical hacking to combat cyber threats at any scaleKey FeaturesAdvice on how to use the ethical hacking methodology and thought process to perform a successful ethical hackAn exploration of the various stages of an ethical hack and the tools related to each phaseYou'll get the most out of this book ifYou want to learn more about ethical hackingYou already work as part of a security team, blue team, purple team or as a security analyst $1 (Bbut that$1 (Bs not a prerequisiteYou want to become familiar with the same skills and tools that potential attackers may use to breach your system and identify security vulnerabilitiesYou have a solid understanding of cloud computing and networkingHands-on exercises at the end of each chapter to ensure you solidify what you$1 (Bve learnt and get experience with the toolsBook DescriptionThe Ethical Hacking Workshop will teach you how to perform ethical hacking and provide you with hands-on experience using relevant tools. By exploring the thought process involved in ethical hacking and the various techniques you can use to obtain results, you'll gain a deep understanding of how to leverage these skills effectively. Throughout this book, you'll learn how to conduct a successful ethical hack, how to use the tools correctly, and how to interpret the results to enhance your environment's security. By the end of the book, you'll be well-versed in ethical hacking and equipped with the skills and knowledge necessary to safeguard your enterprise against cyber-attacks.What you will learnThe key differences between encryption algorithms, hashing algorithms and cryptography standardsHow to capture and analyze network trafficBest practices in performing recon in cloudHow to perform scanning techniques and network mappingLeveraging various top tools to perform privilege escalation, lateral movement, and implant backdoorsHow to clear tracks and evade detectionWho this book is forThe book is intended to be read by those who are looking to learn about ethical hacking. Individuals who are part of security teams, blue teams, purple teams and not limited to security analysts will benefit from this book. The readers should have a good understanding of cloud computing and networkings